Ductility performance of reinforced rubberised concrete beams incorporating burnt clay powder - David Sinkhonde (Elsevier, 2021)
Application of rubberised concrete in earthquake prone areas is of significant importance. Although investigations have been conducted to research on the ductility of rubberised concrete, the behaviour of rubberised concrete with Burnt Clay Brick Powder (BCBP) is not well understood. This paper captures the ductility behaviour of rubberised concrete containing BCBP. In this study, 3 beams were investigated in flexure while the other 3 beams were made to fail in shear and flexure. For the beams that failed in flexure, ductility of concrete beams containing 5% BCBP and 10% Waste Tire Rubber (WTR) improved by 23.47% compared to control beam. This increase in ductility was evidenced with only 15.31% reduction in flexural load. Moreover, the beam containing 5% BCBP and 10% WTR failing in shear and flexure exhibited 14.59% ductility improvement with 16.33% load reduction in comparison to the control beam. Eventually, the study concluded that it is possible to achieve improved ductility without substantial loss in ultimate failure load by using 5% BCBP and 10% WTR. Such properties demonstrated that this rubberised concrete with 5% BCBP can be used in seismic applications.